The Influence of Locus of Control, Smartphone Use, and Parents Social Support Towards Academic Procrastination in Vocational School at Bekasi City for The Academic Year 2023/2024 - Putriwangi, Gusti Muazarah; Sumiati, Ati; Fauzi, Achmad (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study aims to determine the influence of locus of control, smartphone use, and parents’ social support on academic procrastination among vocational school students majoring in accounting and finance institution in Bekasi City. This study uses a quantitative method with a questionnaire instrument. The population of this study was tenth-grade vocational school students majoring in accounting and finance institution in Bekasi City with an affordable population of 309 students. The sampling technique for this study was probability sampling using the proportionate stratified random sampling method and obtained a sample of 174 respondents. The analysis methods for this study are validity test, reliability test, data description analysis, prerequisite tests analysis, multiple linear regression analysis, and hypothesis test analysis (t-test, F-test, and coefficient of determination test). The results of this study show that (1) locus of control has a negative and significant effect on academic procrastination, (2) smartphone use has a positive and significant effect on academic procrastination, (3) parent’s social support has a negative and significant effect on academic procrastination, and (4) locus of control, smartphone use, and parent’s social support simultaneously have a significant effect on academic procrastination.